A Comparison between E-learning Resources currently used in Project Management Online Training - Roxana Postelnicu (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
E-learning has become popular among learners of all ages and different domains, while project management is one of the many practices that have been impacted by the 21st-century online digital environment. The goal of this paper is to explore and compare current e-learning resources that help online train and continuously educate IT project managers in software developing industries. As to the methodology, a qualitative method will be used for applied research: inductive approach - inductive reasoning. Each identified resource will be provided with a narrative description based on process-oriented interrogations. In the end, a comparison will be made between the existing online platforms offering project management related courses, in order to help conclude which e-learning materials are best to be used by project managers nowadays, taking into consideration their educational needs.
Keywords: M15; 330; e-learning platforms; online courses; education; project management training